Burkina Faso : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper examines Burkina Faso's banking system and traces its macro-financial linkages. The analysis builds upon the macro-financial linkages work conducted in the context of the Article IV consultation with the West African Economic and Monetary Union (WAEMU). Overall, the banking system remains profitable and well-capitalized, but its ability to support the real economy needs to be improved if the authorities are to reach their development goals. Moreover, financial inclusion remains low, and despite recent progress on basic access to the financial system, significant barriers to accessing credit remain; particularly for women, rural inhabitants, and the agricultural sector. The available data indicates that the banking system remains well-capitalized and profitable. Systemic risks remain broadly contained, and new banks have come into operation, but there is significant scope to improve the banking system's ability to support the real economy and financial inclusion. Deteriorating security conditions could undermine banks' ability to expand into underserved remote areas.